« Ils finiraient presque par l’aimer ». La controverse autour de la sauvegarde du stade olympique de Lausanne (Ch.-F. Thévenaz, 1949-1954) - Giulia Marino (In Situ)
« They would almost end up loving it” is the title of the Swiss-Francophone Sunday paper published in July 2020. “It” is La Pontaise Olympic Stadium in Lausanne, inaugurated for the 1954 football world cup and intended for demolition for a number of years to allow the construction of an “eco-neighborhood” sponsored by the city. “They” are the residents of Lausanne, who rediscovered this emblematic object when its destruction was decided, finally beginning to take an interest in its history and “spectacular” architecture, designed to impress the judges of the National Olympic Committee during the selection for the 1960 Olympics. In 2008, a scientific study established the undeniable heritage value of the stadium— architectural, technical, social—, an exceptional value confirmed by a commission of specialists organized ad hoc. Today, ten years later, the debate is intense, opposing (over and over again) “nostalgics” and “progressives". The collective memory is challenged by a contested use value. “An exceptional work” that deserves to be saved, or an obsolete building that hinders the development of “sustainable city”? At a time when the Helsinki stadium (built in 1936) is being carefully restored, in line with the standards of monumental heritage, and, on the other hand, an icon of engineering, Pier Luigi Nervi’s stadium in Florence (built in 1932), is under threat, the recent history of the Olympic Stadium in Lausanne is an example of the dilemmas and questions surrounding the preservation the of large 20th century urban infrastructures.